Perceptions of Poultry Farmers on the Use of Growth Enhancers in Poultry Production in Rivers State, Nigeria - Favour Alapu; Angela Emodi (Journal of Agricultural Extension)
Proper feeding of domesticated animals is necessary in other to meet the nutritional needs of a growing human population. The study examined the perceptions of poultry farmers on the use of growth enhancers in poultry production in Rivers State, Nigeria. Simple random sampling was used to select 120 farmers from each group of the twenty (20) poultry farmers groups in the FADAMA and RIV CARE projects in Rivers State. Data were collected through a structured questionnaire and analyzed using percentage and mean scores. Results revealed that farmers (90.0%) were aware of the use of growth enhancers and pelleting additives (64.1%), feeding enzymes 64.1%, and antibiotics (51.3%) were the major growth enhancers used by poultry farmers. The perceptions of poultry farmers on the use of growth enhancers in poultry production were improved growth (x?=3.83), better nutrient utilization (x?=3.44), higher production yield (x? =3.32), consumer preference for organic products (x?=3.35), safety and quality concerns (x? =3.05), antibiotic resistance (x? =2.92) amongst others. The study concluded that for an increase in the use of growth enhancers in poultry production, there is need for stakeholders in poultry production to empower farmers with the knowledge needed to harness the potentials of feed enhancers.